White crane - Fussell, Sandy; James, Rhian Nest, 1962- (Somerville, Mass. : Candlewick Press, 2010)
Even though he has only one leg, Niya Moto is studying to be a samurai, and his five fellow-students are similarly burdened, but sensei Ki-Yaga, an ancient but legendary warrior, teaches them not only physical skills but mental and spiritual ones as well, so that they are well-equipped to face their most formidable opponents at the annual Samurai Games.
Keywords: Samurai -- Juvenile fiction; People with disabilities -- Juvenile fiction; Contests -- Juvenile fiction; Schools -- Juvenile fiction; Japan -- Juvenile fiction; Samurai -- Fiction; People with disabilities -- Fiction; Contests -- Fiction; Schools -- Fiction; Japan -- Fiction